2015
DOI: 10.1021/acs.energyfuels.5b02080
|View full text |Cite
|
Sign up to set email alerts
|

Hg Speciation in Petroleum Hydrocarbons with Emphasis on the Reactivity of Hg Particles

Abstract: Particulate HgS is generally thought to be the most abundant Hg species in stored petroleum hydrocarbons stocked onshore. It is also assumed that due to its high stability constant, HgS is chemically inert. However, results from the current study would suggest otherwise. Firstly, a comparison study of the analytical performance of ICP-MS and CV-AFS with respect to matrix effect, showed no significant difference in the measured Hg concentrations in studied samples when CV-AFS is used in the alkali mode. Subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 35 publications
(73 reference statements)
1
31
0
Order By: Relevance
“…Following water samples, the most frequently analyzed material for mercury was seafood samples, such as fish, shrimp, and seaweed. A few studies reported the determination of mercury in various environmental samples, such as petroleum hydrocarbons [ 88 ], human hair [ 89 , 90 ], phosphate fertilizers [ 53 ], glycerin [ 91 ], sediments [ 55 , 92 , 93 ], cosmetics [ 94 ], living cells [ 66 , 95 ], and tobacco [ 67 ]. However, a few methods [ 74 , 81 , 87 , 96 101 ] did not report their applicability to natural samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following water samples, the most frequently analyzed material for mercury was seafood samples, such as fish, shrimp, and seaweed. A few studies reported the determination of mercury in various environmental samples, such as petroleum hydrocarbons [ 88 ], human hair [ 89 , 90 ], phosphate fertilizers [ 53 ], glycerin [ 91 ], sediments [ 55 , 92 , 93 ], cosmetics [ 94 ], living cells [ 66 , 95 ], and tobacco [ 67 ]. However, a few methods [ 74 , 81 , 87 , 96 101 ] did not report their applicability to natural samples.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, electrochemical methods had a higher degree of selectivity and did not suffer from interference from other ions. Determination of the level of interference was not performed by a large number of authors [ 45 47 , 53 , 55 , 59 , 60 , 62 , 63 , 69 , 88 , 91 , 92 , 102 106 ] who determined mercury with spectrometric instruments. However, those using electrochemical instruments, spectrophotometers, or spectrofluorometers largely reported the level of interfering ion(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, there is a need to identify exactly which species of mercury are present. The total amount of Hg should fulfil the following mass balance equation 8 :…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, direct liquid total analysis of petroleum samples by ICP-MS requires conscientious selection of the introduction technique to prevent large quantities of carbon arriving to the plasma, either by low-flow nebulizers, cooled spray chambers or alternative procedures. [11][12][13] Direct injection by thermal vaporization and ICP-MS was also employed. Unfortunately, matrix effects and signal-drifts caused by co-elution of hydrocarbons demanded for the application of isotope dilution using 34 S-labelled volatile standards.…”
mentioning
confidence: 99%